THE IMPROVING OF THE STUDENTS' WRITING SKILLS BY USING DIARY WRITING STRATEGY - Rositasari, Tri; Saraswaty, Dwi Rara; Larasati, Finza; Warnia, Wiske (Universitas Muhammadiyah Palembang, 2024)
The purpose of this research is to use a writing diary strategy to improve the writing skill of class IX students of SMP Muhammadiyah 4 Palembang. The method used in this research is the descriptive analysis method. The population of this study was all students of class IX at SMP Muhammadiyah 4 Palembang. The total population is 176 students, and the samples taken are 29 students from 176 students using the purposive sampling method. The use of data was carried out using a written test pre-test and post-test, and the results of the analysis showed that writing diaries improved students' writing skills. The average student score increased after applying diary writing, before applying diary writing the student's pre-test score could be said to be 68.55 where the average value was at intervals of 65.79 which means moderate. However, after the post-test was carried out using the instrument test, there were no students in the very low category with an average score of 84.4 where the average value was in the interval 80-89 which means high. This shows that the level of student's ability after applying the habit of writing books is in the high category.